Nations in the worldview of the poet Salm - Soran Bahaulddin Ezzulddin; Ibrahim Ahmad Shwani (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study is titled: "Nations in the Worldview of the Poet Salm." It is an attempt to express Salim's thoughts about the neighboring Kurdish nations especially the nations that ruled the Kurds, which Salem (1805-1869) has his own point of view about them. If prediction is part of the individual's worldview, then Salm's worldview for the Kurd's future in between the Turk, Persian and Arab of the nations around the Kurds was a correct prediction, He will be disappointed with everyone, this is a time when there was a gathering umbrella of nations called Islamic Ummah (Islamic people) and caliphates, the days that followed after Salm untill now were a manifestation of the truth, have shown that these nations have been a problem for the Kurds. Therefore, when he looked in any nation, the question for Salm was how they are for the Kurds, and sometimes Salm's worldview for the Kurd neighboring nations was as much a reaction, was less a deep reading of the characteristics of those nations. Nations occupy a wide space in Salm's poetry and worldview, first of all, mention of Roman, Turk, Persian, Arab, Turkman, Russian, English, Armenian, and Tatar, as well as those religions with a national identity, such as Jews, and Yezidis, mentioned them in the same circumstances.